PENGEMBANGAN ATTITUDES TOWARD HEALTH CARE TEAMS SCALE PADA KULIAH KERJA NYATA PROFESI KESEHATAN - Sulastien, Herni; Syahrul, Syahrul; Kadar, Kusrini S (Jurnal Ilmiah Kesehatan Keperawatan, 2018)
Field work in Health profession is the implementation of field activities on health students (medicine, nursing, dentistry, physiotherapy, nutrition, and pharmacy). In the event, there was cooperation between student groups of health with IPE approach to solve health problems in the community. However, there is no standard tool for measuring student attitudes to cooperate in IPE implementation groups on field work of this health profession. Therefore, researchers want to develop tools to see the implementation of this IPE activity. The purpose to produce ATHCT in Indonesian version and modified to evaluate the implementation of IPEC activity on field work of health profession. Method: This research uses delphi method to get input from expert experts about appropriate tools to measure IPE activity on field work of Health profession. Before the delphi method begins, begins with the process of translating tools from English to Indonesian. Further entry in the stage of delphi consisting of three stages with expert experts consisted of: lecturer nursing, medical professors, and lecturers physiotherapy. The results obtained from the Delphi method of round I are: 57% of experts issued two statement items that are not in accordance with the condition of KKN health profession. In the second round there was an agreement of experts that there are 12 items statement that can be used to evaluate the implementation of IPE on field work health profession. Round III researchers sent back the ATHCT questionnaire to experts and received expert approval that the tools could be used to evaluate the implementation of the IPEC activities on professional field work. Discussion: Delphi technique is very suitable if you want to do research on instrument development. This study there is no sitting together among experts to agree on the instrument together to enable differences in perception.Â Â Key word : attitude, field work, interprofessional,careÂ